Student Engagement dalam Sharing task dan Jumping Task untuk Mengembangkan Kemampuan Kolaborasi dan Komunikasi - M Muis; Siti Djuwariyah; Aslikhatin Aslikhatin; Nur Fauziyah (Universitas Muhammadiyah Gresik, 2022)
This research is descriptive qualitative. The research stages refer to the implementation of Lesson Study which consists of four stages, namely Plan, Open Class, Reflectiion and Redesign with 4 cycles. The research subjects were students of class 8D UPT SMP Negeri 1 Gresik semester 1 for the academic year 2021-2022. The number of students was 31 students consisting of 14 males and 17 females. The reason for choosing 8D is because students are less active in engaging in learning activities, lack of discussion so that collaboration and communication can be said to be very low. Data collection tools are observation and documentation. In conclusion, there has been a change in the collaboration and communication abilities of students after the learning was carried out by giving sharing tasks and jumping task where the increase in collaboration and communication skills was shown in activities such as presenting the findings/observations, using graphs, tables, and symbols for present information, accept joint decisions, receive awards, criticism and suggestions, understand, negotiate, take into account different views to reach a solution flexible problem in cooperation, always compromise with the team to solve the problem. Keywords: collaboration, communication, sharing tasks and jumping tasks